Optimizing Citrix XenDesktop for high performance : successfully deploy XenDesktop sites for a high performance Virtual Desktop Infrastructure (VDI) /: successfully deploy XenDesktop sites for a high performance Virtual Desktop Infrastructure (VDI). (2015) - Ellrod, Craig Thomas
No abstract available